Discourses and Semantic Tropes of the Philosophical Explication of Video Games - Belyaev, Dmitry Anatolyevich; Belyaeva, Ulyana Pavlovna (Problemos, 2019)
The article explores one of the most remarkable and dynamic phenomena of modern technoculture – video games. It reconstructs the genesis of the philosophical discourse on video games, exposing the main difficulties arising in making the definitions. Special importance is attached to the critical comparative analysis of the major strategies for the philosophical explication of video games. With the aid of the method of comparative-historical reconstruction and a structuralist approach, the essential correlations between the essential definition of a video game and the ontological systems of Plato, the Gnostics, G. Berkeley, E. Kant, as well as post-modern philosophy was established. The research results in formulating a model-integrative definition of a video game.
Keywords: video games; narratologists; ludologists; game studies